2017
DOI: 10.1364/oe.25.010464
|View full text |Cite
|
Sign up to set email alerts
|

Improved optical absorption in visible wavelength range for silicon solar cells via texturing with nanopyramid arrays

Abstract: Surface-texture with silicon (Si) nanopyramid arrays has been considered as a promising choice for extremely high performance solar cells due to their excellent anti-reflective effects and inherent low parasitic surface areas. However, the current techniques of fabricating Si nanopyramid arrays are always complicated and cost-ineffective. Here, a high throughput nanosphere patterning method is developed to form periodic upright nanopyramid (UNP) arrays in wafer-scale. A direct comparison with the state-of-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Fabrication of Nanostructured Si : The UNP‐textured silicon was etched from single‐crystal, n‐type Si (100) silicon wafer (1–3 Ω cm, 270 ± 20 µm thickness). The UNP arrays were fabricated by scalable colloidal lithography and anisotropic wet etch technique, which was reported in the previous work . Closely packed monolayer of 1.4 µm polystyrene (PS) nanosphere was prepared by micropropulsive injection technique, then the assembled monolayer of PS sphere was subjected to reactive‐ion etching process in the atmosphere mixed of O 2 and Ar to reduce the diameter of the PS spheres.…”
Section: Methodsmentioning
confidence: 99%
“…Fabrication of Nanostructured Si : The UNP‐textured silicon was etched from single‐crystal, n‐type Si (100) silicon wafer (1–3 Ω cm, 270 ± 20 µm thickness). The UNP arrays were fabricated by scalable colloidal lithography and anisotropic wet etch technique, which was reported in the previous work . Closely packed monolayer of 1.4 µm polystyrene (PS) nanosphere was prepared by micropropulsive injection technique, then the assembled monolayer of PS sphere was subjected to reactive‐ion etching process in the atmosphere mixed of O 2 and Ar to reduce the diameter of the PS spheres.…”
Section: Methodsmentioning
confidence: 99%
“…Most recently, due to the requirement of low cost and dimension controllable properties of the nanostructure, self-assembled nano-preparation method has been proposed, and the commercial value outstands in the widespread use of photovoltaic devices [13]- [16] and light-emitting diodes [17], [18]. Moreover, some achieves have shown that nanostructure with gradually changed sidewall profiles can effectively improve the optical performance of the solar cells [19]- [22]. Guan Zisheng et al made an inverted pyramid structured c-Si solar cell by controlling the metal assisted chemical etching process, which improved the Jsc by 0.22 mA/cm 2 when comparing with the best positive pyramid structured c-Si solar cell [20].…”
Section: Introductionmentioning
confidence: 99%
“…Fan Zhiyong et al used the pre-imprinting anodization AAO (PIA-AAO) process to prepare amorphous silicon solar cells on nano-cone plastic substrates, the light trapping efficiency reached as high as two folds of the similar planar devices [21]. Gao Pingqi et al proposed a high-throughput nanosphere patterning method to form a periodic upright nanopyramid arrays on the silicon surface, resulting a 1.35 mA/cm 2 Jsc improvement by comparing with the state-of-the-art random pyramids textured one [22]. However, most of these studies are based on single morphology parameter of the structures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its low process threshold and cost-effective performance, this is the most mature production process in the photovoltaic industry for decades. An anisotropic wet chemical etch is typically utilized to form a micro-sized pyramidal structure as a light-harvesting structure using different etch rates of silicon crystals at <100> and <111> surfaces [14]. It has been shown that a randomly sized pyramid array surface can have better light-harvesting efficiency and therefore a better absorption coefficient than planar and single sized pyramid array surfaces [15].…”
Section: Introductionmentioning
confidence: 99%